Regional Exhumation and Tectonic History of the Shanxi Rift and Taihangshan, North China. Issue 3 (23rd March 2021) - Clinkscales, Christopher; Kapp, Paul; Thomson, Stuart; Wang, Houqi; Laskowski, Andrew; Orme, Devon A.; Pullen, Alex
Abstract: This study presents a comprehensive low‐temperature thermochronometric data set from the Shanxi Rift, Taihangshan, and eastern Ordos block in North China, including new apatite fission track and apatite (U‐Th‐Sm)/He data and published apatite and zircon fission track and (U‐Th‐Sm)/He data. We use these data and new thermal history inversion models to reveal that the Shanxi Rift and Taihangshan experienced an increase in cooling rates between ca. 110–70 Ma and ca. 50–30 Ma. A preceding ca. 160–135 Ma cooling event is generally restricted to the western rift margin in the Lüliangshan and Hengshan. In contrast, the ca. 50–30 Ma cooling event was widespread and occurred coevally with the opening of the Bohai Basin and slip across the NNE‐striking Eastern Taihangshan fault. In the southern rift zone, however, exhumation beginning ca. 50 Ma was likely associated with fault block uplift across the ESE–striking Qinling and Huashan faults, which accompanied the extensional opening of the Weihe Graben. Coeval fault slip along the NNE–striking Eastern Taihangshan faults and ESE–striking Qinling and Huashan faults was associated with NW‐SE extension in North China related to oblique subduction of the Pacific plate under Eastern Asia and slow convergence rates. The Shanxi Rift is commonly attributed to Late Miocene and younger extension, but our new thermochronologic data do not precisely record the onset of rifting. However, our inversion models do suggest ≤∼50°C of Neogene–Quaternary cooling, consistent with ≤∼2 km of footwall uplift across most range‐bounding faults. Key Points: Fault blocks of the Shanxi Rift have experienced <∼2 km of footwall uplift since the Miocene Low‐temperature thermochronometric data record region‐wide cooling events at ca. 110–70 Ma and 50–30 M, prior to development of the modern Shanxi Rift Exhumation at ca. 50–30 Ma is coeval with the formation of the Bohai and Weihe basins during a period of regional NW‐SE extension